'Elite' career-changers and their experience of initial teacher education. Issue 2 (15th March 2017) - Wilkins, Chris
Abstract: This study explores the motivation of 'high-status' professionals to change career and enter teaching, and their experience of undertaking initial teacher education (ITE) programmes in England. The study builds on previous research which found that career-changers are disproportionately more likely to fail to complete their ITE studies, and that those who do complete the transition into teaching frequently experience frustration with some aspects of induction and often feel undervalued by their new colleagues. The participants in this study were largely positive about most aspects of their ITE experience, and felt their professional background enabled them to be resilient when faced with the challenges of transitioning from being an expert in one domain to novice in another. However, they report variable experiences of mentoring, and for some, a sense of their previous experience being under-appreciated by ITE tutors and schools. The study also finds little evidence of personalisation built into ITE programmes to take account of the distinctive needs of career-changers. This paper concludes that the current policy focus adopted in England and in many other countries on entry quality may detract from the more fundamental issue of ensuring ITE programmes provide the flexible and personalised professional learning environments that enable a diverse range of entrants to flourish.